MORALITY, GENDER REPRESENTATION AND DESCRIPTION OF RACIAL POLICY IN THE TV SERIES OF GAME OF THRONES AND STRANGER THINGS - Vukojević, Borislav; Vučetić, Vuk (Politeia, 2020)
The paper examines the thesis about the elements of gender, race, and morality discrimination in popular media culture, with an emphasis on two television series: Game of Thrones and Stranger Things. The main research question is whether the elements of discrimination that are most commonly found in Hollywood productions can be found in these series as well. Using the method of multi-perspective cultural studies and looking at the subject dealt with through the constructivist paradigm, the authors conclude that in popular culture, such as the aforementioned series, there are elements of discrimination: morality is dominantly nihilistic, with few characters possessing moral integrity; racial discrimination is evident both in the story and in the cast selection; gender representation is stereotyped, men get a lot more space. The authors argue that it is impossible to explore current media effects on audiences, but it is possible to interpret messages and meanings in popular media culture.
Keywords: Game of thrones; Stranger things; discrimination; media effects; gender roles